Mechanical Characterization of Aluminum Sandwich Structures with Woven-Ply Pineapple Leaf/Glass Fiber-Reinforced Hybrid Composite Core. Issue 1 (31st December 2023) - Ng, Lin Feng; Yahya, Mohd Yazid; Muthukumar, Chandrasekar; Woo, Xiu Juan; Muhaimin, Abdul Halim; Majid, Rohah A.
ABSTRACT: Fiber-metal laminates consisting of alternating metal and fiber-reinforced polymer layers have displayed remarkable performance in several engineering applications. This work aims to identify the feasibility of incorporating pineapple leaf fiber to partially supersede glass fiber in thermoplastic-based fiber-metal laminates. Fiber-metal laminates made of pineapple leaf/glass/polypropylene/aluminum were fabricated using the hot press molding technique. The tensile, flexural, Charpy impact and quasi-static indentation tests were performed. The findings indicated that the hybridization of glass with pineapple leaf fibers improved the mechanical properties of the laminates. The results are particularly promising in [G/P/G] laminates in which their tensile and flexural strengths are 38.98% and 20.19% higher than [P/P/P] laminates. In addition, the Charpy impact strengths of [G/P/G] laminates are also 236.66% and 175.68% greater than those of [P/P/P] laminates. In terms of indentation properties, the maximum indentation forces of [G/P/G] laminates are 16.71% and 13.76% higher than those of [P/P/P] laminates at indenter diameters of 12.7 and 20.0 mm, respectively. Interestingly, in-plane and out-of-plane properties of [G/P/G] laminates were comparable to [G/G/G] laminates. Thus, it is anticipated that the hybridization concept could escalate the utilization of natural fibers as a potential reinforcement for engineering applications.